ICT Policy Implementation as Correlate for Achieving Educational Sustainability: Approaching Development in Multi ICT Dimensions (Journal of Information Technology and Digital World, 2022)
The advancement in the national policy with regard to Information Communication Technologies (ICTs) in education has been updated by the demand for consistent and corresponding implementation of national policy on ICT for tertiary education in Nigeria. The policy identified the criticality of ICTs in the fulfillment of the national technology aspirations in the perspective of attaining sustainable development goals. The current research surveyed the level of ICT deployment in Hussaini Adamu Federal Polytechnic in relation to core ICT policy implementation framework and provided justification for the adoption of top ICT infrastructure in the digital-centric academic environment. The survey adopted quantitative research methodology to obtain information from four hundred and twenty respondents randomly selected from four units in the institution. The result of the research indicated that ICTs implementation within the educational management is fundamental to students’ academic accomplishment, job satisfaction, productivity, and globalization, becoming unmistakably obligatory for governments, teachers, and management of institutions in the contemporary time to prioritize ICTs and incorporate electronic changes for opportunities in the digital age.
Keywords: ICT Policy Implementation; ICT Infrastructure; Information System; Educational Management; Sustainable Development; E-Learning Education